Evaluación in vitro del detartrol sobre esmalte, prismas del esmalte, bandas de hunter-schreger y penachos adamantinos o de linderer, mediante microscopia electrónica de barrido y cortes transversales. (2020)
A descriptive investigation with healthy central teeth, premolars and third molars is carried out to determine the possible reactions that Detartrol causes on tooth enamel, Hunter-Schreger bands and Adamantine or Linderer Penachos. The purpose of this investigation is to identify the reaction of detartrol when it is applied to the enamel structure The material under study in this investigation is composed of hydrochloric acid, iodine and ethanol. The first compound of this product, has already been studied in other investigations, which are presented as the main antecedents of this study, considering its similarity of compounds and effects. The objectives of this research are determined by scanning electron microscopy and cross sections; comparing the teeth exposed to Detartrol with those that were not. The results show that after the material under study makes contact with the superficial or internal part of the structure of the tooth enamel, it does cause damage. However, it should be taken into account that the damage increases or decreases depending on the time in which the product is allowed to act. Then, based on the stated objectives, if the product is applied for 60 seconds, the enamel prisms, the Hunter bands and the adamantine penachos open or expand, losing their natural form and generating nonconformity, which in posterity leads to tooth sensitivity. However, if the Detartrol acts for 15 seconds, it does not penetrate this internal structure, but it causes tooth enamel attrition on its surface.